UJI EFEK ANTIDIARE INFUSA KULIT BUAH PISANG KEPOK (Musa paradisiaca L. forma typical) TERHADAP MENCIT JANTAN YANG DIINDUKSI OLEUM RICINI - Revita Saputri; Risti Hadiyanti; Eka Fitri Susiani (BORNEO JOURNAL OF PHARMASCIENTECH, 2020)
The use of plants as a treatment for diarrhea is a potentialsource as an alternativeto traditional medicine.Kepok bananapeel(Musa paradisiaca L.)is one of thenatural can be used as antidiarrheal because they contain flavonoids, tannins andsaponins. The purpose of this study to determine the infusion of kepok bananapeel has an antidiarrheal effect on mice induced with oleum ricini and todetermine the infusion dose of kepok banana peel which provides the bestantidiarrheal effect. Kepok banana peel extracted by infusion method.Testing ofthe antidiare effect of Kepok banana peel infusion in oleum ricini induces mice.The study was divided into 5 groups : group 1 (control negative), group 2 (controlpositif loperamid 2mg), group 3 (dose of kepok banana peel infusion 5% b/v),group 4 (dose of kepok banana peel infusion 10% b/v),and group 5 (dose of kepokbanana peel infusion 15% b/v). Antidiarrheal observation in every 30 minutes for4 hours including the frequency diarrheaand consistency of faecal.The results offrequencydiarrhea showed weresignificantlydifferent betweengroup 5and group 1which can be seen fromdecreased frequency of diarrhea. The results ofconsistencyfaecalshowedthat the infusion of kepok banana peel infusion 15% b/vimproved consistency of faecalto be normal at 180 minute observation. Kepokbanana peel infusion 15% b/v showed the best antidiarrheal effect comparedtokepok banana peel infusion 5% b/v and 10% b/v.